Analisis strategi penanganan kredit pemilikan rumah bermasalah pada Bank Tabungan Negara Kantor Cabang Tulungagung - Ulinuha, Ulfa (Maliki Interdisciplinary Journal, 2023)
MORTGAGE is one of Bank BTN’s products that can solve housing problems in Indonesia. This study aims to analyze the strategy for handling problematic home ownership loans at Bank Tabungan Negara (BTN) Tulungagung Office. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with Loan Service Staff at Bank Tabungan Negara Tulungagung. The results of the study show that Bank Tabungan Negara Tulungagung Sub-Branch Office has implemented various strategies for handling problematic home ownership loans. However, there are still some obstacles in the implementation of these strategies. To overcome these obstacles, Bank Tabungan Negara Tulungagung Sub-Branch Office needs to strengthen its credit analysis and improve customer education to avoid bad loans. Therefore, it is expected that Bank Tabungan Negara Tulungagung can be more effective in handling problematic home ownership loans and increase customer trust in the bank.